β-Glucans: Relationships between Modification, Conformation and Functional Activities - Qiang Wang; Xiaojing Sheng; Aimin Shi; Hui Hu; Ying Yang; Li Liu; Ling Fei; Hongzhi Liu (Molecules, 2017)
β-glucan is a type of polysaccharide which widely exists in bacteria, fungi, algae, and plants, and has been well known for its biological activities such as enhancing immunity, antitumor, antibacterial, antiviral, and wound healing activities. The conformation of β-glucan plays a crucial role on its biological activities. Therefore, β-glucans obtained from different sources, while sharing the same basic structures, often show different bioactivities. The basic structure and inter-molecular forces of polysaccharides can be changed by modification, which leads to the conformational transformation in solution that can directly affect bioactivity. In this review, we will first determine different ways to modify β-glucan molecules including physical methods, chemical methods, and biological methods, and then reveal the relationship of the flexible helix form of the molecule chain and the helix conformation to their bioactivities. Last, we summarize the scientific challenges to modifying β-glucan’s conformation and functional activity, and discuss its potential future development.